Emerging Trends in the Social and Behavioral Sciences 2015
DOI: 10.1002/9781118900772.etrds0117
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Decision‐Making: Contemporary Research on the Role of the Self

Abstract: How do people decide when facing dilemmas that pit self‐interested gains against ethical values? We highlight two key principles from contemporary behavioral research: (i) people are more willing to act unethically when they can convince themselves that their behavior does not reflect poorly on their moral character and (ii) people tend to be content with an “ethical enough” self‐image. We examine how these principles shed light on the antecedents and consequences of ethical behavior, emphasizing situational d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Research has repeatedly shown how the need to preserve a moral self-image inhibits people from acting as unethically as they are tempted to (for reviews, see, e.g., Monin & Jordan, 2009; Shu & Effron, in press; Zhong, Liljenquist, & Cain, 2009). For example, most people tend to cheat a little to satisfy their material desires, but not so much that they come to see themselves as dishonest (Bolton, Katok, & Zwick, 1998; Mazar, Amir, & Ariely, 2008; Shalvi, Handgraaf, & De Dreu, 2011); they also cheat more when doing so seems less diagnostic of their moral character (Bryan et al, 2013; Von Hippel, Lakin, & Shakarchi, 2005; Wiltermuth, 2011).…”
Section: Cheating Scarcity and Anticipatory Regretmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has repeatedly shown how the need to preserve a moral self-image inhibits people from acting as unethically as they are tempted to (for reviews, see, e.g., Monin & Jordan, 2009; Shu & Effron, in press; Zhong, Liljenquist, & Cain, 2009). For example, most people tend to cheat a little to satisfy their material desires, but not so much that they come to see themselves as dishonest (Bolton, Katok, & Zwick, 1998; Mazar, Amir, & Ariely, 2008; Shalvi, Handgraaf, & De Dreu, 2011); they also cheat more when doing so seems less diagnostic of their moral character (Bryan et al, 2013; Von Hippel, Lakin, & Shakarchi, 2005; Wiltermuth, 2011).…”
Section: Cheating Scarcity and Anticipatory Regretmentioning
confidence: 99%
“…In each of these examples, people face a repeated sequence of similar ethical quandaries in which they must choose whether to increase their own outcomes by cheating or to preserve a desirable self-concept by upholding their moral obligations. Although a great deal of research has examined the social–psychological factors that influence how people balance these competing concerns (e.g., Ariely, 2012; Bryan, Adams, & Monin, 2013; Shu & Effron, in press; Tenbrunsel & Messick, 2004; Wang & Murnighan, 2014), little is known about the time course of their decisions. Do people cheat at random intervals over a series of choices or do they cheat systematically at certain time points?…”
mentioning
confidence: 99%
“…People have multiple strategies at their disposal to cope with moral identity threats (Shu & Effron, in press). To acquire moral credentials, people can act virtuously (Bradley-Geist et al, 2010; Merritt et al, 2012; Sherman & Gorkin, 1980; Zhong, Liljenquist, & Cain, 2009), distort their memories of their moral track record (Effron et al, 2012; Effron, Monin, & Miller, 2013; M.…”
Section: Discussionmentioning
confidence: 99%